A Training in Preparation of Organic Fertilizer from Wasted Rice Straw in Rice Valtivation Area-Nagari Dilam, Bukit Sundi District, Solok Regency - Okta Suryani; Riga Riga (Fakultas MIPA Universitas Negeri Padang, 2022)
Rice is one of the national mainstay commodities that have an important role in the Indonesian economy, which is also a mainstay crop commodity in Solok Regency. Solok Regency is famous for its high-quality rice. Nagari Dilam, Bukit Sundi District, as a village with a large rice commodity in Solok Regency, most of the residents have a livelihood as rice farmers. To obtain good yields, the material that is needed during the planting process is fertilizer. However, fertilizer problems almost always appear every year in this area. In the last 2 years, farmers have been facing these two problems, including the price of commercial inorganic fertilizers (Urea, SP36, KCl, ZA) which tends to increase. In addition, without realizing it, the intensive use of commercial inorganic fertilizers can cause a decrease in soil fertility and soil organic matter decreases. The idea of using wasted straw came up as a way to solve all of mentioned problems to produce organic fertilizer. A training in preparation of organic fertilizer from wasted straw has been conducted in Nagari Dilam. The produced organic fertilizer has been analyzed for N, P,K containing substance. The fertilizer contains 0.030%, 4.563% and 1.369% of N, P, and K respectively.